PENGELOLAAN SUMBER DAYA MANUSIA PENDIDIKAN ISLAM BERBASIS NILAI-NILAI ISLAMI: Studi Kepustakaan - Wafiq Fadillah Nur; Sudadi; Bahrani (STKIP Subang, 2026)
Human resource management is a crucial factor in determining the quality and success of educational institutions, including those in the context of Islamic education. However, human resource management practices in educational institutions often remain oriented toward modern managerial approaches that emphasize administrative efficiency and have not yet fully integrated Islamic values as their primary foundation. This study aims to analyze and formulate a concept of human resource management in Islamic education based on Islamic values through a literature review approach. This study employs a library research method with data collection techniques involving a literature review of various primary and secondary sources, such as the Qur'an, hadith, scholarly books, and relevant journal articles. Data analysis was conducted using content analysis techniques to identify, categorize, and synthesize the main concepts related to human resource management in Islamic education. The results of the study indicate that human resource management in Islamic education not only encompasses managerial functions such as planning, recruitment, development, and evaluation but must also be grounded in Islamic values such as amanah, ‘adl (justice), syura (consultation), ihsan, itqan, and mas’uliyyah (accountability). The integration of these values forms a holistic human resource management model that combines professionalism, ethics, and spirituality within a single management framework. This study is expected to provide a theoretical contribution to the development of Islamic Education Management studies and serve as a practical reference for Islamic educational institutions in building a high-quality, religious, and public-interest-oriented human resource management system.